Digital Connections: The Dynamics of Loneliness, Interpersonal Trust, and Self-Disclosure on Tinder - Risqi, Salsavira Intania; Dyorita Khoiryasdien, Andhita (Psikostudia : Jurnal Psikologi, 2026)
The evolution of digital technology has profoundly reconfigured patterns of interaction and the architecture of social relations within contemporary society. Nevertheless, the phenomenon of loneliness persists amidst extensive virtual connectivity. This study interrogates the roles of loneliness and interpersonal trust in shaping self-disclosure tendencies among Tinder users in early adulthood (ages 18–40). The sample comprised 100 participants selected via purposive sampling, utilizing the UCLA Loneliness Scale, Interpersonal Trust Scale, and Self-Disclosure Scale as instruments. Multivariate linear regression analysis revealed that the two predictor variables exerted a significant simultaneous influence on self-disclosure (F = 17.556; p = 0.000 < 0.05), with R² = 0.328, indicating that 32.8% of the variance in self-disclosure was accounted for by the predictors. Partial analyses demonstrated significant positive effects of loneliness (β = 0.282; p = 0.004) and interpersonal trust (β = 0.205; p = 0.036), suggesting that elevated levels of loneliness and trust are concomitant with a greater propensity for online self-disclosure. Categorically, female participants exhibited higher tendencies toward self-disclosure.